Sammlung Lafrenz. - André, Carl; Berthot, Jake; Calzolari, Pierpaolo; Deecke, Thomas; Frey, Patrick; Fuchs, Rudi H.; Gastini, Marco; Gerdes, Ludger; Girke, Raimund; Graubner, Gotthard; Graulich, Gerhard; Hentschel, Martin; et al. (Bremen : Neues Museum Weserburg, 1991)
Andre, Carl ; Bauch, Michael ; Berthot, Jake ; Buren, Daniel ; Calzolari, Pierpaolo ; Charlton, Alan ; McCracken, John ; Gastini, Marco ; Gerdes, Ludger ; Girke, Raimund ; Graubner, Gotthard ; Joseph, Peter ; Judd, Donald ; Kawara, On ; Kelly, Ellsworth ; Kiecol, Hubert ; Klingelhöller, Harald ; LeWitt, Sol ; Long, Richard ; Luy, Wolfgang ; Mangold, Robert ; Marden, Brice ; Merz, Mario ; Muñoz, Juan ; Nauman, Bruce ; Noland, Kenneth ; Novros, David ; Palermo, Blinky ; Reineking, James ; Richter, Harald ; Rose, Rolf ; Rückriem, Ulrich ; Ruthenbeck, Reiner ; Ryman, Robert ; Schonzeit, Ben ; Schütte, Thomas ; Serra, Richard ; Therrien, Robert ; Zeniuk, Jerry
biog., ind. tent., gr. tent., bibliog. p. 14-204
Duits
Sammlung Lafrenz, Weserburg Museum für moderne kunst Bremen, 1991
boek